DOI: 10.31274/etd-180810-3241
|View full text |Cite
|
Sign up to set email alerts
|

Fall armyworm Spodoptera frugiperda and black cutworm Agrotis ipsilon susceptibility and avoidance to Bt maize, and implications for global insect resistance management

Abstract: The susceptibility of insect pests to Bacillus thuringiensis (Bt) transgenic crops has been extensively studied, and the behavioral response of these pests is also often characterized. However, discussions regarding the relationship and interaction of antibiosis and antixenosis as protection mechanisms are less common. Pest avoidance of Bt maize (Zea mays) and the linkage, or lack of linkage, of avoidance to susceptibility could influence the design of insect resistance management (IRM) plans. This review exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Corns expressing Cry1Ab (event Bt11 and MON810) or Cry1Fa2 (Event TC1507) demonstrate high efficacy against O. nubilalis [14,20,32], but they are unlikely to have a significant impact on BCW [1,33]. However, either the Cry1Ab × Vip3Aa20 pyramid of Bt11×MIR162 corn or Cry1Fa2 × Cry1Ab × Vip3Aa20 pyramid of TC150 × MON810 × MIR162 corn could provide a much broader-spectrum high dose against H. zea and S. frugiperda [34][35][36][37] as well as BCW [16]. In this study, transgenic corn expressing Vip3Aa19 (events C008 and C010) demonstrated high efficacy to the control of BCW, which suggests that it is a good candidate to be stacked with corn targeting O. furnacalis and Mathimna separata (such as Cry1Ab, Cry1F corn) to obtain a much broader spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corns expressing Cry1Ab (event Bt11 and MON810) or Cry1Fa2 (Event TC1507) demonstrate high efficacy against O. nubilalis [14,20,32], but they are unlikely to have a significant impact on BCW [1,33]. However, either the Cry1Ab × Vip3Aa20 pyramid of Bt11×MIR162 corn or Cry1Fa2 × Cry1Ab × Vip3Aa20 pyramid of TC150 × MON810 × MIR162 corn could provide a much broader-spectrum high dose against H. zea and S. frugiperda [34][35][36][37] as well as BCW [16]. In this study, transgenic corn expressing Vip3Aa19 (events C008 and C010) demonstrated high efficacy to the control of BCW, which suggests that it is a good candidate to be stacked with corn targeting O. furnacalis and Mathimna separata (such as Cry1Ab, Cry1F corn) to obtain a much broader spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic maize producing Bt toxins from soil bacterium Bt provides an effective alternative tool to conventional chemical insecticides for the control of major coleopteran and lepidopteran insect pests, with little adverse effect to beneficial insects and other non-target organisms [13][14][15]. Several laboratory studies and greenhouse trials have shown that the currently developed Bt maize lines were highly toxic to BCW, and event TC1507 expressing the Cry1F protein has made it possible to control a broader spectrum of lepidopteran pests including BCW [16]. Syngenta developed transgenic cotton VipCot TM expressing vip3Aa19 gene, which is highly toxic to BCW [17].…”
Section: Introductionmentioning
confidence: 99%